Assessing additive interactions of heat wave, fine particulate matter, and ozone on cardiovascular mortality in a typical cold region of China: A time-stratified case-crossover study - Jinghao Wan; Mingzhao She; Hanhan Wang; Lixin Zheng; Xinyue Yu; Yuqian Song; Zhongran Wang; Min Li; Xu Han; Haibo Zhou; Zhifeng Xing; Xiao Bai; et al. (International Journal of Hygiene and Environmental Health, 2026)

Valorization of massive waste dolomite powders via a binary aggregate system in cement mortars: Multiscale analysis and sustainable insights - Haibo Hu; Xiaosong Ma; Anming She; Yongqi Wei; Junqing Zuo; Wu Yao; Min Wu (Sustainable Chemistry and Pharmacy, 2026)

An evolutionary game-based optimization approach for multi-tier collaborative capacity allocation in industrial chains with chain master enterprise - Mingzhe She; Xiao Lai; Yanshan Gao; Chenze Wang; Xiaohan Zhang; Zhifang Xu; Min Liu; Fei Qiao (Swarm and Evolutionary Computation, 2026)

Amino-functionalized covalent organic framework-carboxylated carbon nanotubes via covalent bonding for sensitive Tau electrochemical immunosensing - Ping He; Wen-Tao Li; A-Min Zhu; Si-Yuan An; Jun-Ping Ma; She-Ying Dong; Yuan-Zhen Zhou; Jun-Jie Zhu (Chemical Engineering Journal, 2026)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Seasonal and regional variability of lipophilic marine phycotoxins in eutrophic coastal waters of the South China Sea - Min Liu; Liyan Deng; Yan Wang; Xiaodong Wang; Sen Du; Zhicai She; Zhenjun Kang; Qingxia Liu; Peng Wu; Zexing Kuang; Lingxiang Zhu; Jiajun Wu; et al. (Harmful Algae, 2025)

Polarized electric field and defect-induced energy storage effects enhancing the piezocatalytic and piezo-photocatalytic activities of Bi25FeO40 crystals - Xiongtao Wu; Guoqiang Tan; Wenlong Liu; Bixin Zhang; Linxin Guo; Sizhe Fan; Chunyan Zeng; Ao Xia; Huijun Ren; Min Wang; Liaona She; Fan Gao; et al. (Journal of Environmental Chemical Engineering, 2025)

ABA is involved in OsDSR3-mediated regulation of alkali tolerance in rice - Xuping Lu; Weifang Min; Yangmengfei She; Tinglu Liao; Donghao Xiao; Lei Tian; Peifu Li; Chengke Luo (Journal of Plant Physiology, 2025)

Electrospinning preparation of NaA zeolite composite polyacrylonitrile membranes (NaA@PANMs) and studying on adsorption performance for Sr2+ - Yu Liu; Min Yi; Tao Han; Xinlong Li; Linqiao Qin; Yu She; Erna Wei; Kaituo Wang (Environmental Research, 2025)

Efficient and inexpensive preparation of mesoporous silica microspheres and their highly selective adsorption-cycling performance for Ga(III) in acidic solutions - Yu She; Lin Shao; Min Yi; Yong Fang; Linqiao Qin; Yu Liu; Xinpeng Wang; Kaituo Wang (Chemical Engineering Journal, 2025)

Piezoelectric-photothermal catalytic degradation of BPA by Cs0.32WO3 nanorods in dark-full spectrum - Chunyan Zeng; Guoqiang Tan; Bixin Zhang; Linxin Guo; Xiongtao Wu; Sizhe Fan; Wenlong Liu; Min Wang; Ao Xia; Huijun Ren; Liaona She; Yaxiong Yang; et al. (Journal of Environmental Chemical Engineering, 2025)

Geochemical Modelling of Fluid-Rock Interactions in Shallow Buried Carbonate Reservoirs Based on the Water Bath Instrument - Jiayi Ma; Anjiang Shen; Shuyun Xie; Min She; Huayun Tang; Emmanuel John M. Carranza; Tianfu Zhang (Journal of Earth Science, 2025)

ALFIN-like proteins link histone H3K4me3 to H2A ubiquitination and coordinate diverse chromatin modifications in Arabidopsis - Xiao-Min Su; Dan-Yang Yuan; Na Liu; Zhao-Chen Zhang; Minqi Yang; Lin Li; She Chen; Yue Zhou; Xin-Jian He (Molecular Plant, 2025)

Construction of energy storage heterojunction and enhancement mechanism of dark and full-spectrum energy storage piezoelectric catalysis - Bixin Zhang; Guoqiang Tan; Wenlong Liu; Xiongtao Wu; Linxin Guo; Zeqiong Wang; Chunyan Zeng; Ying Liu; Tian Liu; Qian Yang; Ao Xia; Huijun Ren; et al. (Chemical Engineering Journal, 2025)

Hydrogen-Bonded organic framework Containing stacked Cu2+ for photocatalytic reduction of CO2 to C2H4 - Mengmeng Zhou; Debo Ding; Yansong Shi; Keke Wang; Qin Wang; Xiahe Chen; Hai-Min Shen; Teng-Shuo Zhang; Yun-Fang Yang; Jiexiang Xia; Huaming Li; Yuanbin She (Chemical Engineering Journal, 2025)

Effect of calcination temperature on the presence pattern of calcium ions in slag-based geopolymer microspheres and visible light photocatalytic degradation of tetracycline hydrochloride - Linqiao Qin; Lin Shao; Min Yi; Yu She; Yu Liu; Wenwen Chen; Yuxiao Jiang; Kaituo Wang (Journal of Environmental Chemical Engineering, 2024)

Development and preservation mechanism of deep and ultra-deep carbonate reservoirs - Anjiang Shen; Anping Hu; Zhanfeng Qiao; Jianfeng Zheng; Min She; Liyin Pan (Science China Earth Sciences, 2024)

Dissolution kinetics and heterogeneous evolution of dolomite with different pore structures - Jiayi Ma; Shuyun Xie; Min She; Tianfu Zhang; Anjiang Shen; Zhiwei Kuang; Yue Zhou; Zhengyu Bao (Applied Geochemistry, 2024)

Local microenvironment modulation of zirconium-porphyrinic frameworks for CO2 reduction - Xue Zhao; Chang-Yan Zhu; Heng Rao; Dong-Ying Du; Min Zhang; Ping She; Li Li; Jun-Sheng Qin (Chemical Engineering Journal, 2024)

Cardenolide glycosides sensitize gefitinib-induced apoptosis in non-small cell lung cancer: inhibition of Na+/K+-ATPase serving as a switch-on mechanism - Chi-Min Du; Wohn-Jenn Leu; Yi-Huei Jiang; She-Hung Chan; Ih-Sheng Chen; Hsun-Shuo Chang; Lih-Ching Hsu; Jui-Ling Hsu; Jih-Hwa Guh (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

A DUF966 gene family member OsDSR3 positively regulates alkali stress tolerance in rice - Xuping Lu; Yan Li; Maryam Akhtar; Caixia Liu; Tianli Ma; Weifang Min; Xiaorong Bai; Yangmengfei She; Liang Chen; Lei Tian; Peifu Li; Chengke Luo (Plant Science, 2024)

Functional identification and characterization of two flavonoid glycosyltransferases ZmUGT84A3 and ZmUGT84A4 from maize - Zhao Ke; Dengyu Zheng; Meng She; Shipeng Zhang; Zhongyi Wu; Min Lu; Zhongbao Zhang (Journal of Plant Biochemistry and Biotechnology, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Thermodynamic analysis for new solutions of data center cooling with adsorption refrigeration and heat pipe - Xuekun She; Xunfeng Li; Min Xu; Jingzhi Zhou; Junlin Chen; Xiulan Huai; Zhixia He (International Journal of Refrigeration, 2024)

Biochemical and Transcriptome Analysis Reveals Pigment Biosynthesis Influenced Chlorina Leaf Formation in Anoectochilus roxburghii (Wall.) Lindl - Xiu-Xian Ye; Yi-Quan Chen; Jian-She Wu; Huai-Qin Zhong; Bing Lin; Min-Ling Huang; Rong-Hui Fan (Biochemical Genetics, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Dolomite dissolution and porosity enhancement simulation with acetic acid: Insights into the influence of temperature and ionic effects - Min She; Jintong Liang; Yuzhen Lv; Anping Hu; Zhanfeng Qiao (Applied Geochemistry, 2024)

Unraveling the genomic diversity and ecological potential of the genus Demequina: insights from comparative analysis of different saline niche strains - Lei Gao; Bao-Zhu Fang; Chun-Yan Lu; Kun-Hui Hong; Xin-Yu Huang; Ting-Ting She; Min Xiao; Wen-Jun Li (Frontiers in Marine Science, 2023)
During an investigation of the culturable microbial diversity of sediments with salinity from tidal flats and saline lake, seven strains of the genus Demequina were harvested. The genomic analysis and physiological characteristics of strains of this genus have unveiled their significant potential in degrading complex carbon source such as lignin, hemicellulose, chitin, and oligosaccharides. In addition, these strains show potential abilities in nitrite ammonification and sulfide oxidation. These findings not only improved our understanding of their metabolic model, but also provided valuable insights into their ecological roles. Four new species of the genus Demequina are described: Demequina litoralis sp. nov., with SYSU T00192 T designated as the type species; Demequina zhanjiangensis sp. nov., with SYSU T00b26 T as the type species; Demequina lignilytica sp. nov., with SYSU T00068 T as the type species; and Demequina muriae sp. nov., with EGI L300058 T as the type species. Additionally, strains SYSU T0a273, SYSU T00039-1, and SYSU T00039 are identified as different strains of Demequina lignilytica . Our study thus sheds light on the diversity, biological significance, and ecological contribution of the Demequina genus in different habitats.

Seismic fragility assessment of aqueduct bent structures subjected to mainshock-aftershock sequences - Min Du; Sherong Zhang; Chao Wang; Lei She; Jiabei Li; Tong Lu (Engineering Structures, 2023)

Precisely modulate interfacial Bi-O bridge bond in Co-TCPP/Bi3O4Br to trigger long-lasting charge separation for boosting CO2 photoreduction - Yi Zhang; Fangyu Guo; Keke Wang; Jun Di; Bokki Min; Huiyuan Zhu; Hailong Chen; Yu-Xiang Weng; Jiayu Dai; Yuanbin She; Jiexiang Xia; Huaming Li (Chemical Engineering Journal, 2023)

Retraction notice to “Sedimentary characteristics and origin of dolomitic ooids of the terminal Ediacaran Dengying Formation at Yulin (Chongqing, South China)” [Palaeogeography, Palaeoclimatology, Palaeoecology 544 (2020) 109601] - Dongfang Zhao; Guang Hu; Lichao Wang; Fei Li; Xiucheng Tan; Min She; Wenji Zhang; Zhanfeng Qiao; Xiaofang Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The suppressed expression of a stress responsive gene 'OsDSR2' enhances rice tolerance in drought and salt stress - Chengke Luo; Maryam Akhtar; Weifang Min; Yasir Alam; Tianli Ma; Yafei Shi; Yangmengfei She; Xuping Lu (Journal of Plant Physiology, 2023)

Influence of capillary condensation on the adsorption of Br2 in flue gas using a super-fine polyester fiber as adsorbent - Hanxi Xiao; Yong Chi; Yusheng You; Min Ren; Lufen Wu; Hongli Li; Manyuan Li; Xue Shi; Yu She; Dongchan Mao (Journal of Cleaner Production, 2023)

A new method for wear estimation of TBM disc cutter based on energy analysis - Lei She; She-rong Zhang; Chao Wang; Yan-long Li; Min Du (Tunnelling and Underground Space Technology, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Cloning and Expression of Sox2 and Sox9 in Embryonic and Gonadal Development of Lutraria sieboldii - Min Lu; Zenghou Xing; Yurui Zhou; Youhou Xu; Huijing Peng; Jie Zou; Solomon Felix Dan; Zhicai She; Pengliang Wang; Jinfeng Liu; Shaomin Qin; Jialin Yang; et al. (Fishes, 2022)
The Sox family plays essential roles as transcription factors in vertebrates; however, little is known about the Sox family in Lutraria sieboldii. L. sieboldii are pleasant to eat with a short growth cycle and have become one of the best bottom-seeded enrichment species in Guang Xi. In this study, Sox2 (named LsSox2) and Sox9 (named LsSox9) from L. sieboldii were cloned, and their expression patterns were analyzed. The length of the LsSox2 gene coding sequence was 1011 bp, encoding 336 amino acids, and LsSox9 was 1449 bp, encoding 482 amino acids. LsSox2 had its highest expression levels in the ovary, which were 356 times those in testis, whereas LsSox9 presented higher expression in testis, which was 6 times more highly expressed than in the ovary. LsSox2 exhibited the highest expression during the morula stage, which was 20 times that of the D-shaped larvae or zygote. LsSox9 exhibited two expression peaks, one at the four-cell stage and the other at the trochophore stage, while the lowest expression was in the zygote. LsSox9 was 73 times more highly expressed in the four-cell stage than in the zygote stage. During gonadal development, LsSox2 presented the highest expression in the mature ovary, which was 756 times more highly expressed than in mature testis. LsSox9 presented higher expression in testis at the emission stage which was 6 times more highly expressed than in the ovary. These results indicate that LsSox2 and LsSox9 may play important roles in embryonic and gonadal development.

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

A Recognition Method of Bactrocera minax (Diptera: Tephritidae) Grooming Behavior via a Multi-Object Tracking and Spatio-Temporal Feature Detection Model - Shengbing Hong; Wei Zhan; Tianyu Dong; Jinhui She; Chao Min; Huazi Huang; Yong Sun (Journal of Insect Behavior, 2022)

Naringin Targets NFKB1 to Alleviate Oxygen-Glucose Deprivation/Reoxygenation–Induced Injury in PC12 Cells Via Modulating HIF-1α/AKT/mTOR-Signaling Pathway - Wei Cao; She-Jun Feng; Min-Chen Kan (Journal of Molecular Neuroscience, 2021)

l-Glutamic acid induced the colonization of high-efficiency nitrogen-fixing strain Ac63 (Azotobacter chroococcum) in roots of Amaranthus tricolor - Yi-Fan Wang; Jun-Feng Wang; Zhi-Min Xu; Shao-Hua She; Jun-Qing Yang; Qu-Sheng Li (Plant and Soil, 2020)

Changes in the Intestinal Microbiota of Gibel Carp (Carassius gibelio) Associated with Cyprinid herpesvirus 2 (CyHV-2) Infection - Rong She; Tong-Tong Li; Dan Luo; Jia-Bao Li; Liu-Yi Yin; Huan Li; Yao-Min Liu; Xiang-Zhen Li; Qi-gui Yan (Current Microbiology, 2017)

Methotrexate affects HMGB1 expression in rheumatoid arthritis, and the downregulation of HMGB1 prevents rheumatoid arthritis progression - Yuan-bo Li; Peng Xu; Ke Xu; Yong-Song Cai; Meng-yao Sun; Le Yang; Jian Sun; She-min Lu (Molecular and Cellular Biochemistry, 2016)

Risk factors for the Long-Term Efficacy, Recurrence, and Metastasis in Small Hepatocellular Carcinomas - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

Clinical Analysis of Internal Fixation Treatment of Intra-articular Calcaneal Fractures with Titanium Plate - Xiao-dong Chen; Chang-chun Zhang; Zhao-cheng Li; Heng Zhang; Xin-she Zhou; Min Deng (Cell Biochemistry and Biophysics, 2015)

Serum CA242, CA199, CA125, CEA, and TSGF are Biomarkers for the Efficacy and Prognosis of Cryoablation in Pancreatic Cancer Patients - Ye Chen; She-Gan Gao; Jian-Min Chen; Gong-Ping Wang; Zeng-Fang Wang; Bo Zhou; Can-Hui Jin; Yan-Tong Yang; Xiao-Shan Feng (Cell Biochemistry and Biophysics, 2015)

Synthesis and anti-cancer activity of a glycosyl library of $$\varvec{N}$$ N -acetylglucosamine-bearing oleanolic acid - Yi-Bing Zeng; Hsin-Min Hsiao; She-Hung Chan; Ying-Hsin Wang; You-Yu Lin; Yu-Hsuan Kuo; Jih-Hwa Guh; Pi-Hui Liang (Molecular Diversity, 2014)

Identification and quantitative detection of Legionella spp. in various aquatic environments by real-time PCR assay - Po-Min Kao; Min-Che Tung; Bing-Mu Hsu; Yi-Chou Chiu; Cheng-Yu She; Shu-Min Shen; Yu-Li Huang; Wen-Chien Huang (Environmental Science and Pollution Research, 2013)

Induction of apoptosis through caspase-independent or caspase-9-dependent pathway in mouse and human osteosarcoma cells by a new nitroxyl spin-labeled derivative of podophyllotoxin - Tuan-Min Yang; She-Ning Qi; Na Zhao; Yu-Jie Yang; Hu-Qin Yuan; Bing Zhang; Shuai Jin (Apoptosis, 2013)

Cutaneous and Mucosal Phaeohyphomycosis Caused by Exophiala spinifera in a Pregnant Patient: Case Report and Literature Review - Le Wang; Xiaodong She; Guixia Lv; Yongnian Shen; Qing Cai; Rong Zeng; Caixia Li; Yiping Ge; Shuwen Deng; G. S. de Hoog; Min Li; Weida Liu (Mycopathologia, 2013)

Reduced apoptosis correlates with enhanced autophagy in synovial tissues of rheumatoid arthritis - Ke Xu; Peng Xu; Jian-Feng Yao; Yin-Gang Zhang; Wei-kun Hou; She-Min Lu (Inflammation Research, 2013)

A Combination Method to Study the Effects of Petroleum on Soil Microbial Activity - Wen Wen She; Jun Yao; Fei Wang; Min Min Cai; Jing Wei Wang; Chang Shun Song (Bulletin of Environmental Contamination and Toxicology, 2013)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Experimental determination of calcite dissolution rates and equilibrium concentrations in deionized water approaching calcite equilibrium - Qingjie Gong; Jun Deng; Qingfei Wang; Liqiang Yang; Min She (Journal of Earth Science, 2010)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Relationships between endothelial nitric oxide synthase gene polymorphisms and osteoporosis in postmenopausal women - Shun-zhi Liu; Hong Yan; Wei-kun Hou; Peng Xu; Juan Tian; Li-fang Tian; Bo-feng Zhu; Jie Ma; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2009)

Influence of HBV gene heterogeneity on the failure of immunization with HBV vaccines in eastern China - She-Lan Liu; Ying Dong; Li Zhang; Min-Wei Li; Jian-er Wo; Li-Wei Lu; Zhen-Juan Chen; Yong-Zhong Wang; Bing Ruan (Archives of Virology, 2009)

Effect of brassinolide on callus growth and regeneration in Spartina patens (Poaceae) - Zhou Lu; Min Huang; Dong-Ping Ge; Yong-Hua Yang; Xiao-Ning Cai; Pei Qin; Jian-Ming She (Plant Cell, Tissue and Organ Culture (PCTOC), 2003)